The Communication Effects of Controversial Sexual Content in Television Programs and Commercials - Bello, Daniel C. and Pitts, Robert E. and Etzel, Michael J. and (Journal of Advertising, 1983)
An experiment utilizing television commercials and programs was employed to examine the effect of controversial sexual content on the communication effectiveness of advertising messages. Three measures of communication effectiveness were employed: interest in commercial, affect toward product, and purchase intent. Results of the experiment suggest controversial sexual content affect the communication effectiveness of advertising in a complex manner. Controversial sexual content in the commercial failed to improve effectiveness, apart from merely making the commercial more interesting, while controversial sexual program content influenced the processing of advertising messages for males but not for females. However, the presence of a significant commercial-by-program interaction for males suggests the actual effect of controversial content in the program environment depends upon the level of controversy present in the commercial.
https://katalog.adlr.link/Record/ai-55-aHR0cHM6Ly93d3cuanN0b3Iub3JnL3N0YWJsZS80MTg4NDUy